The use of satellite data in modeling population dynamics and prevalence of infection in the rodent reservoir of Junin virus - Porcasi, X (2005)
Fil: Porcasi. X. Instituto Gulich, Comisión Nacional de Actividades Espaciales, Centro Espacial Teófilo Tabanera; Argentina.